Analysis Of The Application Of The UTAUT Model In Understanding The Acceptance And Use Of OVO Applications In Malang City: Analisis Penerapan Model UTAUT Dalam Memahami Penerimaan dan Penggunaan Aplikasi OVO di Kota Malang - Kanthi, Yekti Asmoro; Tirtana, Arif; Sulistiyo , Muhadi Aan (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the acceptance and use of OVO applications in Malang City. This study uses the Unified Theory of Acceptance and Use of Technology (UTAUT) Model to explain the acceptance of OVO applications. The constructs used are 4 independent varabels (performance expectancy, effort expectancy, social influence, facilitating conditions) and 1 dependent variabel (behavioral intention). The type of data used is primary data that has been obtained through questionnaires. Sampling using a non-probability technique with aapproach purposive sampling with the criteria used more than 3 times. The number of samples is 100 samples. From the respondent's data obtained were analyzed using multiple regression analysis techniques. Data management is assisted by using the SmartPLS v.3.3.2 software. Based on the data analysis, it can be concluded that: (1) performance expectancy have a positive effect on behavioral intention; (2) effort expectancy have a positive effect on behavioral intention; (3) social influence has aeffect positive on behavioral intention; (4) facilitating conditions have no effect on behavioral intention.